EFFECT OF FETAL BOVINE SERUM (FBS) CONCENTRATION ON THE VIABILITY AND PROLIFERATION OF MESENCHYMAL STEM CELLS (MSCS) IN VITRO - Tri Juanda; Parti Putri (Stem Cell Research and Development Center, Universitas Airlangga, 2026)
Mesenchymal Stem Cells (MSCs) are multipotent stem cells widely utilized in regenerative medicine due to their self-renewal and differentiation capacities. The success of MSC expansion in vitro is strongly influenced by culture conditions, particularly the concentration of Fetal Bovine Serum (FBS) used in the culture medium. This study aimed to evaluate the effect of different FBS concentrations on the viability and proliferation of MSCs in vitro. An experimental laboratory study with a post-test only control group design was conducted using MSC cultures supplemented with 0%, 5%, 10%, and 15% FBS in Dulbecco’s Modified Eagle Medium (DMEM). Cells were incubated for 72 hours under standard culture conditions. Cell viability was assessed using the MTT assay, while proliferation was analyzed using trypan blue exclusion and hemocytometer counting. Statistical analysis was performed using One-Way ANOVA followed by Tukey post hoc test with a significance level of p < 0.05. The results demonstrated that FBS concentration significantly affected MSC viability and proliferation. MSCs cultured with 10% FBS exhibited the highest viability, proliferation rate, and optimal spindle-shaped fibroblast-like morphology with high confluency. In contrast, cells cultured without FBS showed poor attachment, reduced proliferation, and increased apoptotic features. Although the 15% FBS group maintained relatively high viability, proliferation was slightly lower compared to the 10% FBS group. In conclusion, FBS concentration plays a critical role in maintaining MSC growth and survival in vitro, with 10% FBS providing the most optimal culture condition among the tested groups.